Only one isoform of Drosophila melanogaster CTP synthase forms the cytoophidium. - Ghows Azzam; Ji-Long Liu (PLoS Genetics)
CTP synthase is an essential enzyme that plays a key role in energy metabolism. Several independent studies have demonstrated that CTP synthase can form an evolutionarily conserved subcellular structure termed cytoophidium. In budding yeast, there are two isoforms of CTP synthase and both isoforms localize in cytoophidium. However, little is known about the distribution of CTP synthase isoforms in Drosophila melanogaster. Here, we report that three transcripts generated at the CTP synthase gene locus exhibit different expression profiles, and three isoforms encoded by this gene locus show a distinct subcellular distribution. While isoform A localizes in the nucleus, isoform B distributes diffusely in the cytoplasm, and only isoform C forms the cytoophidium. In the two isoform C-specific mutants, cytoophidia disappear in the germline cells. Although isoform A does not localize to the cytoophidium, a mutation disrupting mostly isoform A expression results in the disassembly of cytoophidia. Overexpression of isoform C can induce the growth of the cytoophidium in a cell-autonomous manner. Ectopic expression of the cytoophidium-forming isoform does not cause any defect in the embryos. In addition, we identify that a small segment at the amino terminus of isoform C is necessary but not sufficient for cytoophidium formation. Finally, we demonstrate that an excess of the synthetase domain of CTP synthase disrupts cytoophidium formation. Thus, the study of multiple isoforms of CTP synthase in Drosophila provides a good opportunity to dissect the biogenesis and function of the cytoophidum in a genetically tractable organism.